Synthesis, X-Ray Crystal Structures, and Preliminary Antiproliferative Activities of New s-Triazine-hydroxybenzylidene Hydrazone Derivatives - Assem Barakat; Fardous F. El-Senduny; Zainab Almarhoon; Hessa H. Al-Rasheed; Farid A. Badria; Abdullah Mohammed Al-Majid; Hazem A. Ghabbour; Ayman El-Faham (Journal of Chemistry)
We herein report a new small library of Schiff-base compounds that encompasses s-triazine and (2 or 4)-hydroxylbenzylidene derivatives. These compounds were synthesized through a hydrazone linkage connecting both the s-triazine and hydroxybenzylidene derivatives. The synthetic strategy adopted allowed the synthesis of the target compounds with excellent yields and purities as observed from their NMR (1H and 13C) and elemental analysis. Furthermore, 4f, 5b, and 5f were further confirmed by X-ray single crystal diffraction technique. The preliminary antiproliferative activities for the synthesized compounds were tested against two different cancer cell lines including breast cancer (MCF-7) and colon cancer (HCT-116). From the eighteen compounds, which have been examined, only two derivatives having piperidine moiety showed more selectivity against the two cell lines MCF-7 and HCT-116, while the others showed very weak activity. The position of the hydroxyl group in the benzylidine ring and the substituent on the s-triazine moiety has great effect on the activity of the prepared compounds. The IC50 values for the two derivatives 4a and 5a evaluated against breast cancer cells, very close to those for the chemotherapeutic drug cisplatin, are 27 µM (13.3 µg/mL), 17 µM (8.4 µg/mL), and 20 µM (6 µg/mL) for 4a, 5a, and cisplatin, respectively. These results propose the preliminary antiproliferative activity of these two derivatives may deserve further consideration for development of new derivatives as potent anticancer agents.